Method for Constructing an Individual Educational Route By Completing Tasks for Training Professional Skills in Compiling SQL-queries - Говоров, Антон Игоревич; Говорова, Марина Михайловна; Слизень, Елена Витальевна; Валитова, Юлия Олеговна; Иванов, Сергей Евгеньевич (Computer Tools in Education, 2018)
The article substantiates the importance of the formation of individual educational routes as factor influencing the effectiveness of training and the ability of a specialist to develop skills in professional activities. The expediency of the use of computer simulators in practice-oriented training, particularly in teaching database technologies, is justified, since the existing open educational online courses don’t always provide full-fledged conditions for the development of sustainable practical skills to solve typical professional tasks. The paper proposes a method for constructing an individual educational route during the passage of tasks for training professional skills in compiling SQL-queries, within which the task and student models are described. Based on the proposed models A* algorithm is modified and its conditions for creating the optimal individual educational route are described. Based on the results of a theoretical study, a computer simulator has been implemented for training professional skills in writing SQL-queries using the method of building individual educational routes during the completing tasks for training professional skills in writing SQL-queries and gamification tools and gaming technologies. The results were tested. Based on the analysis of the results, it was concluded that using of the proposed method and algorithms implemented in a computer simulator is expedient.